ANTIBIOTIC RESISTANCE PATTERN OF PSEUDOMONAS AERUGINOSA ISOLATED FROM VARIOUS CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL, PUDUCHERRY - A, KANTHAKUMAR; M, JAYAVARTHINNI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: One of the most common bacteria known to cause nosocomial infection and found to be multidrug-resistant is Pseudomonas aeruginosa. The objective of the study was to know the prevalence of the P. aeruginosa isolates with varied clinical conditions and specimens and to assess the antimicrobial susceptibility patterns of P. aeruginosa as well as its magnitude of multidrug resistance (MDR). Methods: A total of 229 biochemically tested and confirmed isolates of P. aeruginosa from various clinical samples were studied. Antibiotic susceptibility testing was determined by Kirby-Bauer disc diffusion method. Results: Out of the 229 isolates of P. aeruginosa, majority (60.70%) were from pus sample. Resistance to amikacin and tobramycin was 23.6% and 20.1%, ciprofloxacin was 33.2%. Resistance to ceftazidime, cefoperazone and cefepime were 21.8%, 45.9%, and 25.7%. Imipenem and meropenem showed 26.2% and 20.5% resistance, respectively. Resistance to piperacillin was 18.3% while piperacillin-tazobactam was only 13.5%. The MDR was observed in 33.7% of the isolates. Conclusion: There is increased resistance to cephalosporins as compared to aminoglycosides, carbapenems and beta lactamase inhibitor. To restrict the inappropriate use of antimicrobial agents, the development of MDR, needs to be continuously monitored and documented.